# Modus tollens

In propositional logic, modus tollens (/ˈmdəs ˈtɒlɛnz/; MT; also modus tollendo tollens (Latin for "mode that denies by denying")[1] or denying the consequent)[2] is a valid argument form and a rule of inference. It is an application of the general truth that if a statement is true, then so is its contra-positive.

The inference rule modus tollens validates the inference from ${\displaystyle P}$ implies ${\displaystyle Q}$ and the contradictory of ${\displaystyle Q}$ to the contradictory of ${\displaystyle P}$.

The modus tollens rule can be stated formally as:

${\displaystyle {\frac {P\to Q,\neg Q}{\therefore \neg P}}}$

where ${\displaystyle P\to Q}$ stands for the statement "P implies Q". ${\displaystyle \neg Q}$ stands for "it is not the case that Q" (or in brief "not Q"). Then, whenever "${\displaystyle P\to Q}$" and "${\displaystyle \neg Q}$" each appear by themselves as a line of a proof, then "${\displaystyle \neg P}$" can validly be placed on a subsequent line. The history of the inference rule modus tollens goes back to antiquity.[3]

Modus tollens is closely related to modus ponens. There are two similar, but invalid, forms of argument: affirming the consequent and denying the antecedent. See also contraposition and proof by contrapositive.

The first to explicitly describe the argument form modus tollens was Theophrastus.[4]

## Formal notation

The modus tollens rule may be written in sequent notation:

${\displaystyle P\to Q,\neg Q\vdash \neg P}$

where ${\displaystyle \vdash }$ is a metalogical symbol meaning that ${\displaystyle \neg P}$ is a syntactic consequence of ${\displaystyle P\to Q}$ and ${\displaystyle \neg Q}$ in some logical system;

or as the statement of a functional tautology or theorem of propositional logic:

${\displaystyle ((P\to Q)\land \neg Q)\to \neg P}$

where ${\displaystyle P}$ and ${\displaystyle Q}$ are propositions expressed in some formal system;

or including assumptions:

${\displaystyle {\frac {\Gamma \vdash P\to Q~~~\Gamma \vdash \neg Q}{\Gamma \vdash \neg P}}}$

though since the rule does not change the set of assumptions, this is not strictly necessary.

More complex rewritings involving modus tollens are often seen, for instance in set theory:

${\displaystyle P\subseteq Q}$
${\displaystyle x\notin Q}$
${\displaystyle \therefore x\notin P}$

("P is a subset of Q. x is not in Q. Therefore, x is not in P.")

Also in first-order predicate logic:

${\displaystyle \forall x:~P(x)\to Q(x)}$
${\displaystyle \exists x:~\neg Q(x)}$
${\displaystyle \therefore \exists x:~\neg P(x)}$

("For all x if x is P then x is Q. There exists some x that is not Q. Therefore, there exists some x that is not P.")

Strictly speaking these are not instances of modus tollens, but they may be derived from modus tollens using a few extra steps.

## Explanation

Requirements:

1. The argument has two premises.
2. The first premise is a conditional or "if-then" statement, for example that if P then Q.
3. The second premise is that it is not the case that Q.
4. From these two premises, it can be logically concluded that it is not the case that P.

Consider an example:

If the watch-dog detects an intruder, the watch-dog will bark.
The watch-dog did not bark.
Therefore, no intruder was detected by the watch-dog.

Supposing that the premises are both true (the dog will bark if it detects an intruder, and does indeed not bark), it follows that no intruder has been detected. This is a valid argument since it is not possible for the conclusion to be false if the premises are true. (It is conceivable that there may have been an intruder that the dog did not detect, but that does not invalidate the argument; the first premise is "if the watch-dog detects an intruder." The thing of importance is that the dog detects or does not detect an intruder, not whether there is one.)

Another example:

If I am the axe murderer, then I can use an axe.
I cannot use an axe.
Therefore, I am not the axe murderer.

Another example:

If Rex is a chicken, then he is a bird.
Rex is not a bird.
Therefore, Rex is not a chicken.

## Relation to modus ponens

Every use of modus tollens can be converted to a use of modus ponens and one use of transposition to the premise which is a material implication. For example:

If P, then Q. (premise – material implication)
If not Q, then not P. (derived by transposition)
Not Q . (premise)
Therefore, not P. (derived by modus ponens)

Likewise, every use of modus ponens can be converted to a use of modus tollens and transposition.

## Justification via truth table

The validity of modus tollens can be clearly demonstrated through a truth table.

p q p → q
T T T
T F F
F T T
F F T

In instances of modus tollens we assume as premises that p → q is true and q is false. There is only one line of the truth table—the fourth line—which satisfies these two conditions. In this line, p is false. Therefore, in every instance in which p → q is true and q is false, p must also be false.

## Formal proof

### Via disjunctive syllogism

Step Proposition Derivation
1 ${\displaystyle P\rightarrow Q}$ Given
2 ${\displaystyle \neg Q}$ Given
3 ${\displaystyle \neg P\lor Q}$ Material implication (1)
4 ${\displaystyle \neg P}$ Disjunctive syllogism (2,3)

Step Proposition Derivation
1 ${\displaystyle P\rightarrow Q}$ Given
2 ${\displaystyle \neg Q}$ Given
3 ${\displaystyle P}$ Assumption
4 ${\displaystyle Q}$ Modus ponens (1,3)
5 ${\displaystyle Q\land \neg Q}$ Conjunction introduction (2,4)
6 ${\displaystyle \neg P}$ Reductio ad absurdum (3,5)
7 ${\displaystyle \neg Q\rightarrow \neg P}$ Conditional introduction (2,6)

### Via contraposition

Step Proposition Derivation
1 ${\displaystyle P\rightarrow Q}$ Given
2 ${\displaystyle \neg Q}$ Given
3 ${\displaystyle \neg Q\rightarrow \neg P}$ Contraposition (1)
4 ${\displaystyle \neg P}$ Modus ponens (2,3)

## Correspondence to other mathematical frameworks

### Probability calculus

Modus tollens represents an instance of the law of total probability combined with Bayes' theorem expressed as:

${\displaystyle \Pr(P)=\Pr(P\mid Q)\Pr(Q)+\Pr(P\mid \lnot Q)\Pr(\lnot Q)\,}$,

where the conditionals ${\displaystyle \Pr(P\mid Q)}$ and ${\displaystyle \Pr(P\mid \lnot Q)}$ are obtained with (the extended form of) Bayes' theorem expressed as:

${\displaystyle \Pr(P\mid Q)={\frac {\Pr(Q\mid P)\,a(P)}{\Pr(Q\mid P)\,a(P)+\Pr(Q\mid \lnot P)\,a(\lnot P)}}\;\;\;}$ and ${\displaystyle \;\;\;\Pr(P\mid \lnot Q)={\frac {\Pr(\lnot Q\mid P)\,a(P)}{\Pr(\lnot Q\mid P)\,a(P)+\Pr(\lnot Q\mid \lnot P)\,a(\lnot P)}}}$.

In the equations above ${\displaystyle \Pr(Q)}$ denotes the probability of ${\displaystyle Q}$, and ${\displaystyle a(P)}$ denotes the base rate (aka. prior probability) of ${\displaystyle P}$. The conditional probability ${\displaystyle \Pr(Q\mid P)}$ generalizes the logical statement ${\displaystyle P\to Q}$, i.e. in addition to assigning TRUE or FALSE we can also assign any probability to the statement. Assume that ${\displaystyle \Pr(Q)=1}$ is equivalent to ${\displaystyle Q}$ being TRUE, and that ${\displaystyle \Pr(Q)=0}$ is equivalent to ${\displaystyle Q}$ being FALSE. It is then easy to see that ${\displaystyle \Pr(P)=0}$ when ${\displaystyle \Pr(Q\mid P)=1}$ and ${\displaystyle \Pr(Q)=0}$. This is because ${\displaystyle \Pr(\lnot Q\mid P)=1-\Pr(Q\mid P)=0}$ so that ${\displaystyle \Pr(P\mid \lnot Q)=0}$ in the last equation. Therefore, the product terms in the first equation always have a zero factor so that ${\displaystyle \Pr(P)=0}$ which is equivalent to ${\displaystyle P}$ being FALSE. Hence, the law of total probability combined with Bayes' theorem represents a generalization of modus tollens [5].

### Subjective logic

Modus tollens represents an instance of the abduction operator in subjective logic expressed as:

${\displaystyle \omega _{P{\tilde {\|}}Q}^{A}=(\omega _{Q|P}^{A},\omega _{Q|\lnot P}^{A}){\widetilde {\circledcirc }}(a_{P},\,\omega _{Q}^{A})\,}$,

where ${\displaystyle \omega _{Q}^{A}}$ denotes the subjective opinion about ${\displaystyle Q}$, and ${\displaystyle (\omega _{Q|P}^{A},\omega _{Q|\lnot P}^{A})}$ denotes a pair of binomial conditional opinions, as expressed by source ${\displaystyle A}$. The parameter ${\displaystyle a_{P}}$ denotes the base rate (aka. the prior probability) of ${\displaystyle P}$. The abduced marginal opinion on ${\displaystyle P}$ is denoted ${\displaystyle \omega _{P{\tilde {\|}}Q}^{A}}$. The conditional opinion ${\displaystyle \omega _{Q|P}^{A}}$ generalizes the logical statement ${\displaystyle P\to Q}$, i.e. in addition to assigning TRUE or FALSE the source ${\displaystyle A}$ can assign any subjective opinion to the statement. The case where ${\displaystyle \omega _{Q}^{A}}$ is an absolute TRUE opinion is equivalent to source ${\displaystyle A}$ saying that ${\displaystyle Q}$ is TRUE, and the case where ${\displaystyle \omega _{Q}^{A}}$ is an absolute FALSE opinion is equivalent to source ${\displaystyle A}$ saying that ${\displaystyle Q}$ is FALSE. The abduction operator ${\displaystyle {\widetilde {\circledcirc }}}$ of subjective logic produces an absolute FALSE abduced opinion ${\displaystyle \omega _{P{\widetilde {\|}}Q}^{A}}$ when the conditional opinion ${\displaystyle \omega _{Q|P}^{A}}$ is absolute TRUE and the consequent opinion ${\displaystyle \omega _{Q}^{A}}$ is absolute FALSE. Hence, subjective logic abduction represents a generalization of both modus tollens and of the Law of total probability combined with Bayes' theorem [6].